Cobalamin‐Catalysed Chemical Reactions: Probing the Role of the Nucleotide Loop. Issue 2 (10th October 2018) - Karczewski, Maksymilian; Ociepa, Michał; Gryko, Dorota
Abstract : The nucleotide loop in the vitamin B12 structure affects its biological and physicochemical properties, but its role in cobalamin‐catalysed reactions still remains disputable. Herein, we show the synthesis of a series of model compounds including N ‐methylcobalamin (NMICbl) in a base‐off form with the nucleotide attached. The structure‐activity relationship studies reveal that in the studied cobalamin‐catalysed reaction, the reduction step is not rate‐determining. Abstract : A series of vitamin B12 cobalamin derivative complexes with a nucleotide attached were synthesized, in order to determine the role of the nucleotide loop within catalysis. Structure‐activity relationship studies reveal that the reduction step is not rate‐determining.